Ghana : Adjustment and Growth, 1983-91 - Kapur, Ishan (Occasional Papers; Occasional Paper, 1991)
The first sub-Saharan African country to pursue broad economic and structural reform - aided by external finance and technical aid - Ghana is an example of adjustment with growth. Ghana's experience, discussed in this paper, illustrates the need for complementary policy actions and the right sequencing and speed of reforms.